ANALISIS PENDAPATAN PETANI KARET DAN SISTEM PENGOLAHAN BAHAN OLAH KARET (BOKAR) (Kasus di Desa Tanah Abang Kecamatan Batanghari Leko Kabupaten Musi Banyuasin) (JASEP, 2016)
This study aims to: (1) Calculated rubber farmers income tenants and owners of tenant farmers in the village of Tanah Abang subdistrict Batang Leko and (2). reviewing the material processing system Olah Rubber (Bokar) processing by the farmers in the village of Tanah Abang subdistrict Batang Leko. The sampling used in this study is the method of stratified random lopsided "disproportionate stratified random sampling" which samples are taken randomly with a disproportionate number of which is composed of two layers. The results showed that the average income received rubber farmers tilling owner of Rp.1.325.384,00 / ha per month and the income of peasants Rp. 807 227 / ha per month. Bokar processing of rubber farmers in the village of Tanah Abang subdistrict Batang Hari Leko Musi Banyuasin not in accordance with the type and quality of the ingredients mixing and processing system bokar the rubber farmers that causes lower quality bokar rubber farmers.